2001
DOI: 10.1053/jhep.2001.20534
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Liver Biopsy in Chronic Hepatitis C

Abstract: Hepatitis C virus (HCV) is a major cause of chronic liver disease worldwide, affecting 175 million people globally. Over 80% of acutely infected patients go on to develop chronicity, but only 20% to 25% will develop end-stage liver disease and its complications. The sequelae of HCV-induced chronic liver disease accounts for 8,000 to 10,000 deaths annually in the United States and is currently the leading indication for liver transplantation. To date, there are no accurate noninvasive markers of disease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
2
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(158 citation statements)
references
References 25 publications
8
140
2
8
Order By: Relevance
“…Фиброзная ткань труднее втягивается в биопсийную иглу, и поэтому в пунктате может быть представлена в недостаточном количестве. Таким обра-зом, отсутствие признаков патологического процесса в гепатобиоптате не исключает его наличия у пациента [6,71]. E. трактов, в то время как для верной оценки степени вос-паления и стадии фиброза необходим образец ткани, содержащий как минимум 11 портальных трактов [21].…”
Section: показания к проведению биопсии печени у детейunclassified
“…Фиброзная ткань труднее втягивается в биопсийную иглу, и поэтому в пунктате может быть представлена в недостаточном количестве. Таким обра-зом, отсутствие признаков патологического процесса в гепатобиоптате не исключает его наличия у пациента [6,71]. E. трактов, в то время как для верной оценки степени вос-паления и стадии фиброза необходим образец ткани, содержащий как минимум 11 портальных трактов [21].…”
Section: показания к проведению биопсии печени у детейunclassified
“…In addition, clinical laboratory measurements and radiologic diagnostic approaches have not been developed to evaluate and further grade the severity of early stage liver cirrhosis, which occurs in most clinical cases. A previous study showed that only a small number of the Hepatitis C virus (HCV)-infected patients with liver cirrhosis could be definitively diagnosed based on clinical signs, as well as laboratory and imaging analyses (Saadeh et al 2001). Many important physiologic and biochemical metabolic processes occur in the liver.…”
Section: Hplc-msmentioning
confidence: 99%
“…If liver biopsy is not contraindicated, it should be offered to all patients who would be considered candidates for antiviral therapy. The large multicentre randomised control treatment trials have included patients with moderate to severe liver damage, and the evidence base for treatment and response rates to therapy are based on this subgroup [7][8][9] . Patients in whom liver biopsy is contraindicated (eg haemophiliacs) must be assessed on clinical grounds alone.…”
Section: Examination and Investigationsmentioning
confidence: 99%